PROFESSIONAL EXAMINATIONS. - Chamberlain, Henry T. (The Accounting Review, 1941)
The article presents problems prepared by the Board of Examiners of the American Institute of Accountants, which were presented as the first part of the examination in accounting theory and practice held in the cooperating states on May 15th and 16th. One of the questions requires the students to prepare intelligible columnar work sheets showing the consolidation of the accounts, minority interests, earned surplus at beginning, and profit and loss from the provided balance sheets, profit and loss accounts and other data. Another question provided data for the preparation of a statement of operating results of the Zinc Mining and Milling Company in October that will show the operations on the company's own account and its activities in furnishing milling services to others, both for zinc and for lead concentrates. All supporting schedules had to be presented. Computations were to be carried the third decimal The students were required to observe and offer suggestions concerning, the form and substance of the accounts presented, and the treatment therein of depreciation on appreciation.